Human Head Stiffness Rendering - Minggao, Wei (Université d'Ottawa / University of Ottawa, 2015)
The technology of haptics rendering has greatly enriched development in Multimedia applications, such as teleoperation, gaming, medical and etc., because it makes the virtual object touchable by the human operator(s) in real world. Human head stiffness rendering is significant in haptic interactive applications as it defines the degree of reality in physical interaction of a human avatar created in virtual environment. In a similar research, the haptic rendering approach has two main types: 1) Haptic Information Integration and 2) Deformation Simulation. However, the complexity in anatomic and geometric structure of a human head makes the rendering procedure challenging because of the issues of accuracy and efficiency. In this work, we propose a hybrid method to render the appropriate stiffness property onto a 3D head polygon mesh of an individual user by firstly studying human head's sophisticated deformation behaviour and then rendering such behaviour as the resultant stiffness property on the polygon mesh. The stiffness property is estimated from a semantically registered and shape-adapted skull template mesh as a reference and modeled from soft tissue's deformation behaviour in a nonlinear Finite Element Method (FEM) framework. To render the stiffness property, our method consists of different procedures, including 3D facial landmark detection, models semantic registration using Iterative Closest Point (ICP) technique, adaptive shape modification processed with a modified Weighted Free-Form Deformation (FFD) and FEM Simulation. After the stiffness property is rendered on a head polygon mesh, we perform a user study by inviting participants to experience the haptic feedback rendered from our results. According to the participants' feedback, the head polygon mesh's stiffness property is properly rendered as it satisfies their expectation.
Keywords: Multimedia haptics; stiffness property rendering; models semantic registration; adaptive shape modification; nonlinear finite element modeling